ADHD and medicalization: consideration of the senses and meanings of symptoms presented by children diagnosed - Schicotti, Rosana Vera de Oliveira; Abrão, Jorge Luís Ferreira [UNESP]; Gouveia Júnior, Sérgio Augusto [UNESP] (Nuances Estudos Sobre Educacao, 2014)
The present paper is a reflection on the diagnosis of Attention Deficit Hyperactivity Disorder (ADHD) and its relations to the process of medicalization as well as the meanings and perspectives apprehended through three case studies of children diagnosed with such disorder in a doctoral research in which the main purpose was to understand the meanings and peculiarities of ADHD symptomatology .We’ve utilized the model of qualitative research, grounded in psychoanalytic perspective, and conducted the psychodiagnosis for three children who were referred for psychological treatment. The survey found that those children had few experiences of both continence and frustration tolerance. It was evidenced how the school uses the logic of medicalization to try solving the problems with their children when it came to the school dimension. The variety of symptomatic manifestations and psychic dynamics presented by the cases that were studied revealed the weaknesses and inconsistencies of the referred diagnosis.

El presente trabajo es una reflexión sobre el diagnóstico de Trastorno por Déficit de Atención con Hiperactividad (ADHD), su relación con el proceso de medicalización y los significados presentados en tres casos de niños diagnosticados con este trastorno en una investigación doctoral cuyo objetivo principal fue comprender los significados y las peculiaridades de la sintomatología del ADHD. Trabajamos con el modelo de la investigación cualitativa, basada en la perspectiva psicoanalítica, y llevamos a cabo el psicodiagnóstico de tres niños que fueron referidos para tratamiento psicológico. La encuesta encontró que los niños tuvierán pocas experiencias de contención e interdición. Con respecto a la escuela, se evidencia cómo ella utiliza el pensamiento medicalizado para tratar de resolver los problemas con sus niños. La variedad de manifestaciones sintomáticas y dinámicas psíquicas que presentáran los casos estudiados, puso de manifiesto las debilidades e inconsistencias de ese diagnóstico.

O presente trabalho é uma reflexão acerca do diagnóstico do Transtorno do Déficit de Atenção e Hiperatividade (TDAH), suas relações com o processo de medicalização e os sentidos e significados apreendidos em três casos de crianças diagnosticadas com esse transtorno em uma pesquisa de doutorado cujo objetivo principal foi compreender os significados da sintomatologia do TDAH. Trabalhamos com o modelo de pesquisa qualitativa, fundamentado na psicanálise, e realizamos o psicodiagnóstico de três crianças que foram encaminhadas para atendimento psicológico. A pesquisa constatou que as crianças tiveram poucas experiências de continência e tolerância à frustração. No tocante à dimensão escolar, ficou evidenciado o quanto a escola utiliza a lógica medicalizante para solucionar os problemas encontrados com suas crianças. A variedade das manifestações sintomáticas e das dinâmicas psíquicas apresentadas pelos casos estudados, revelaram as fragilidades e incongruências do referido diagnóstico.
ADHD and medicalization: consideration of the senses and meanings of symptoms presented by children diagnosed
ADHD y medicalización: examen de los sentidos y significados de síntomas presentados por los niños diagnosticados
Keywords: Lack of attention disorder with hyperactivity; Childhood; Medicalization; Trastorno por déficit de atención con hiperactividad; Niñez; Medicalización; Distúrbio da falta de atenção com hiperatividade; Infância; Medicalização